A Correlation among the COVID-19 Spread, Particulate Matters, and Angiotensin-Converting Enzyme 2: A Review. (12th May 2021) - Khan, Zafran; Ualiyeva, Daniya; Khan, Asaf; Zaman, Nasib; Sapkota, Sanjeep; Khan, Ayub; Ali, Babar; Ghafoor, Dawood
Abstract : Air pollution (AP) is one of the leading causes of health risks because it causes widespread morbidity and mortality every year. Its impact on the environment includes acid rain and decreased visibility, but more importantly, it also has an impact on human health. The rise of COVID-19 demonstrates the cost of failing to manage AP. COVID-19 can be spread through the air, and atmospheric particulate matters (PMs) can create a good atmosphere for the long-distance spread of the virus. Moreover, these PMs can cause lung cell inflammation, thereby increasing sensitivity and the severity of symptoms in COVID-19 patients. In this study, we emphasized the potential role of PMs in the spread of COVID-19. The relationship among COVID-19, PMs, and angiotensin-converting enzyme 2 (ACE2) (receptor involved in virus entry into lung cells and inflammation) was also summarized.